PEMIKIRAN NASHIRUDDIN AL-THUSI TENTANG EKONOMI - Siti Fauziyah; Ali Samsuri (Program Studi Ekonomi Syariah, 2024)
Abstract Nasruddin Tusi's economic thought represents a significant contribution to the development of medieval Islamic economic thought. In his renowned work,